PEMBERIAN REWARD DAN PUNISHMENT YANG DIBERIKAN GURU DALAM PEMBELAJARAN PADA MASA PANDEMIC - Ismi Mariani; Fadhila Yusri (KOLONI, 2022)
This research is motivated because there are still students who are less focused in the learning process. Plus the difference in the ability of teachers to apply appropriate learning methods to students. reward and punishment in learning is one of the efforts made by teachers to increase students' enthusiasm for learning, namely the provision of reinforcement in the form of rewards and punishments. Positive reinforcement in the form of rewards is given as a form of appreciation from educators. Departing from these problems, in this study the author focuses on the form of reward and punishment given by the teacher in learning during the pandemic at SDN 02 Koto Tangah Batu Hampa. This study uses a qualitative approach with qualitative descriptive research, namely research that goes to the field to understand and observe the phenomena that occur at SDN 02 Koto Tangah Batu Hampa Jorong Piladang. Data collection techniques are observation, interviews and documentation. While the data analysis is done by examining the existing data then reducing the data, presenting the data and drawing conclusions and the final stage of this data analysis is to determine the validity of the data. The results obtained indicate that the form of reward is not only in the form of material but can also be in the form of words of praise, giving smiles and also giving gifts. While the form of punishment given by the teacher when students violate the rules at school is in the form of punishment, standing in front of the class, standing outside the classroom, doing assignments outside and in front of the class, and also in the form of a reprimand. Keywords: Reward, Punishment, Teaching